TRADEMARK PROTECTION AND SUSTAINABLE DEVELOPMENT: A COMPARATIVE STUDY OF INDONESIA, OMAN, AND THE PHILIPPINES - I Gede Agus Kurniawan; Putu Aras Samsithawrati; Fradhana Putra Disantara; Souad Ahmed Ezzerouali; Princess Alyssa Tee-anastacio (Faculty of Law, Universitas Lampung, 2026)
Trademark protection is a fundamental element of intellectual property law that supports innovation, economic growth, and legal certainty while increasingly contributing to sustainable development through fair business practices, local market strengthening, and sustainable employment. This study examines trademark protection regimes in Indonesia, Oman, and the Philippines using a normative and comparative legal approach to assess their contribution to the Sustainable Development Goals, particularly in relation to economic growth, innovation, and institutional strength. The findings show that although all three countries formally recognize the importance of trademark protection, they differ significantly in regulatory design and enforcement, with Indonesia facing persistent enforcement challenges, Oman demonstrating strong legal structure but limited practical effectiveness, and the Philippines adopting a more adaptive and institutionally robust approach. The study concludes that trademark protection can function as an effective tool for sustainable development if supported by stronger institutional capacity, greater alignment with international standards, and enhanced regional cooperation.